COMPLICATED FORMS OF PYELONEPHRITIS IN CHILDREN - M. D. Bakradze; S. N. Zorkin; E. I. Zelikovich; O. V. Kustova; G. M. Dvoryakovskaya; V. K. Tatochenko; I. L. Chashchina (Педиатрическая фармакология, 2013)
The article is dedicated to purulent renal lesion which is considered to be very rare in children. Case reports on complicated and purulent pyelonephritis forms in children are only singular. The authors present their own experience of observing 10 such clinical cases. Clinical manifestations, peculiarities of laboratory parameters’ change and also the visualization efficiency of kidney changes discovered with instrumental methods are considered in detail. Antibacterial therapy peculiarities are also shown. The authors offer the criteria, according to which a complicated urinary tract infection course may be suspected with high confidence.